KPC-2-Producing Carbapenem-Resistant Klebsiella pneumoniae of the Uncommon ST29 Type Carrying OXA-926, a Novel Narrow-Spectrum OXA β-Lactamase - Liu, Lina; Feng, Yu; Wei, Li; Xiao, Yuling; Zong, Zhiyong (Frontiers in Microbiology, 2021)
We characterized a carbapenem-resistant Klebsiella pneumoniae (CRKP) clinical strain isolated from blood. The isolate, 130002, carries a novel blaOXA gene, blaOXA-926, and belongs to ST29, an uncommon CRKP type. Genome sequencing using both short- and long-read sequencing identified a 94.9-kb self-transmissible IncFII plasmid carrying blaKPC-2. A total of 157 publicly available genomes of the K. pneumoniae ST29 complex (ST29 and its single-allele variants) were retrieved and subjected to phylogenomic analysis. This complex is commonly associated with extended-spectrum β-lactamase gene carriage, in particular blaCTX-M-15 but rarely has carbapenemase genes. The novel plasmid-encoded β-lactamase-encoding gene blaOXA-926 was identified on a 117.8-kb IncFIA-IncFII plasmid, which was transferrable in the presence of the blaKPC-2-carrying plasmid. blaOXA-926 was cloned and MICs of β-lactams in transformants were determined. OXA-926 has a narrow spectrum of activity conferring reduced susceptibility only to piperacillin, piperacillin-tazobactam, and cephalothin. Avibactam cannot fully inhibit OXA-926. blaOXA-926 and its variants have been reported in Klebsiella strains from Asia and Brazil. OXA-926 is closest in sequence identity (89.9%) to a chromosome-encoding OXA-type enzyme of Variovorax guangxiensis. In conclusion, OXA-926 is novel plasmid-borne narrow-spectrum β-lactamase that cannot be fully inhibited by avibactam. It is likely that blaOXA-926 originates from a species closely-related to V. guangxiensis and was introduced into Klebsiella >10 years ago.